2018
DOI: 10.1084/jem.20180570
|View full text |Cite
|
Sign up to set email alerts
|

PRC2 loss induces chemoresistance by repressing apoptosis in T cell acute lymphoblastic leukemia

Abstract: The tendency of mitochondria to undergo or resist BCL2-controlled apoptosis (so-called mitochondrial priming) is a powerful predictor of response to cytotoxic chemotherapy. Fully exploiting this finding will require unraveling the molecular genetics underlying phenotypic variability in mitochondrial priming. Here, we report that mitochondrial apoptosis resistance in T cell acute lymphoblastic leukemia (T-ALL) is mediated by inactivation of polycomb repressive complex 2 (PRC2). In T-ALL clinical specimens, loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 68 publications
(96 reference statements)
1
36
1
Order By: Relevance
“…Although it has been reported that ROS can promote the proliferation and survival of T-ALL cells (42), it is maintained at low levels in the T-ALL leukemia-initiating cells in a mouse model (43). It is also noteworthy that, in more than 50% of the TAL1-positive T-ALL cases, genetic abnormalities in the PI3K-AKT pathway and the NOTCH1-MYC pathway have been observed (4,(8)(9)(10)(11)44), and these pathways can promote several metabolic processes (45). In particular, MYC has been known to promote glutaminolysis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although it has been reported that ROS can promote the proliferation and survival of T-ALL cells (42), it is maintained at low levels in the T-ALL leukemia-initiating cells in a mouse model (43). It is also noteworthy that, in more than 50% of the TAL1-positive T-ALL cases, genetic abnormalities in the PI3K-AKT pathway and the NOTCH1-MYC pathway have been observed (4,(8)(9)(10)(11)44), and these pathways can promote several metabolic processes (45). In particular, MYC has been known to promote glutaminolysis.…”
Section: Discussionmentioning
confidence: 98%
“…TAL1-positive T-ALL constitutes the largest subgroup, accounting for 40-60% of all primary cases (4,(7)(8)(9)(10)(11). One of the known downstream targets of TAL1 in T-ALL cells is ALDH1A2 (12,13), a member of the aldehyde dehydrogenase (ALDH) family of genes that encode oxidoreductases.…”
Section: Introductionmentioning
confidence: 99%
“…A number of EZH2 target genes relating to MM pathogenesis and progression have been characterized; for example, RBPMS [55], which confers chemo-resistance to MM cells. In T-ALL, deficiency of EZH2 and H3K27 tri-methylation results in activation of IGF1, which relates to leukemia stem cell property [64], and CRIP2, which represses apoptosis [65], as well as genes involved in the cytokine signaling pathways and early hematopoietic transcriptional regulators [66]. Importantly, EZH2 may transcriptionally coordinate with other oncogenic regulators.…”
Section: Ezh2 Mediates Lymphoid Oncogenesismentioning
confidence: 99%
“…Loss-of-function mutations of polycomb repressive Table 1). These represent altered: glucocorticoid receptor (GR) expression due to alternative splicing and translation initiation (see text) and function; inhibition of apoptosis by deregulated expression of proteins involved in programmed cell death and through interaction with components of the tumor microenvironment that promote survival signaling; activation of signaling pathways that in a direct or indirect manner alter GR-mediated cell death (see text); and modulation of GR-mediated transcription regulation, thereby altering the expression of critical regulators of GC therapy sensitivity complex (PRC2), which includes EZH2, EED and SUZ12, inhibit mitochondrial apoptosis in immature T lymphocytes, in part through upregulation of HSP90 family chaperone tumor necrosis factor receptorassociated protein 1 (TRAP1) [128] . TRAP1 regulates a variety of cellular processes, and is involved in the protection against DNA damage and apoptosis induced by oxidants and other forms of cellular stress [129] .…”
Section: Gc Resistance By Intrinsic Inhibition Of Apoptosismentioning
confidence: 99%